Influence of dietary niacin on finishing pig performance and meat quality - D E Real; J C Woodworth; M J Webster; B W James; E Alonso; Jim L Nelssen; Michael D Tokach; Robert D Goodband; John A Unruh; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
One hundred forty-four finishing pigs were used to determine the influence of added dietary niacin on their growth performance and meat quality. Gilts grew slower, ate less, and were more efficient than barrows for the entire growth performance period. Increasing dietary niacin levels to 25 g/ton increased ADG in gilts for the first 25 days, but decreased ADG for barrows. No other interactions occurred. From d 25 to 62, ADFI tended to increase for pigs fed up to 100 g/ton niacin, whereas pigs fed 500 g/ton niacin ate less. Dietary niacin level did not significantly affect carcass yield or quality characteristics.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Niacin; Finishing pigs; Meat quality